2006
DOI: 10.1093/aje/kwk034
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Associations between Weather Conditions and Suicide--Evidence against a Classic Hypothesis

Abstract: Psychiatrists, epidemiologists, and sociologists have debated the existence of an association between weather conditions and suicide seasonality since the preliminary statistical investigations in the 19th century. Provided that the effect of weather conditions on suicide operates via a dose-response-like mechanism, time-series (Box-Jenkins) analysis permits an indirect test of the hypothesis that temperature or other weather variables promote higher suicide frequencies in late spring and early summer months. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
55
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 48 publications
7
55
0
2
Order By: Relevance
“…Thus, after removal of seasonal sunshine components, 2 studies have managed to find weak, but significant, positive correlations between the suicide risk and the amount of sunshine on the day of the suicide (i.e., more sunshine, greater risk) [56, 57]. Similar considerations apply to the general lack of a robust association found between variations in the amplitudes of the seasonal spring suicide peaks and ambient temperatures [58], although again several positive associations have been found [29, 59]. Notably, consistent with the Cornell hypothesis of an inciting role of winter depressive symptoms in the genesis of a spring mixed depressive suicidal state, increasingly cloudy winters have been associated with an increasingly elevated suicide risk the following spring [60].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, after removal of seasonal sunshine components, 2 studies have managed to find weak, but significant, positive correlations between the suicide risk and the amount of sunshine on the day of the suicide (i.e., more sunshine, greater risk) [56, 57]. Similar considerations apply to the general lack of a robust association found between variations in the amplitudes of the seasonal spring suicide peaks and ambient temperatures [58], although again several positive associations have been found [29, 59]. Notably, consistent with the Cornell hypothesis of an inciting role of winter depressive symptoms in the genesis of a spring mixed depressive suicidal state, increasingly cloudy winters have been associated with an increasingly elevated suicide risk the following spring [60].…”
Section: Discussionmentioning
confidence: 99%
“…Inne badanie wymienia frustrację oraz kłopoty w pracy i problemy edukacyjne jako główne powody podejmowania prób samobójczych [30]. W omawianym artykule nie odnotowano istotnej różnicy między częstością podejmowania prób samobójczych i samobójstw dokonanych w różnych porach roku, na co wskazywały badania przeprowadzone w USA [39] i Iranie [28]. Być może jest to spowodowane tym, że w Chuzestanie jako prowincji tropikalnej zmiany pór roku nie są odczuwalne, jednak w badaniach prowadzonych w Rosji zanotowano szczytowe natężenie samobójstw w maju i wrześniu [38], a niektóre badania wykazują istotną dodatnią korelację zachowań samobójczych z niektórymi wskaźni-during 2011-2014, was estimated 3.73/100,000 with a minimum and maximum incidence of 2.8 to 6.2/100,000.…”
Section: Discussionunclassified
“…In another study Frustration, work and educational problems were mentioned as the main causes of suicide attempts [30]. In this study, there was no significant difference between seasonal incidence of suicide attempts and completed suicides, as other studies in the United States [39] and Iran [28] confirmed these results This may be because of uniform geographical season of Khuzestan as a tropical Province, however a study in Russia show a peak of suicide in May and September [38], and some studies show a significant positive relationship of suicide behavior Archiwum Medycyny Sądowej i Kryminologii Archives of Forensic Medicine and Criminology kami sezonowymi, takimi jak temperatura i ekspozycja na słońce [18,19] oraz korelację sezonowych prawidło-wości i wahań z maksymalną ilością światła dziennego i calkowitym nasłonecznieniem [20]. W odniesieniu do poszczególnych grup wiekowych najczęściej prób samobójczych oraz samobójstw dokonanych podejmowały się osoby między 18. a 25. rokiem życia, co potwierdzają wyniki wcześniejszych badań [28,29].…”
Section: Discussionunclassified
“…Several individual-level suicide risk factors have been identified (i.e., older age, male gender, psychopathology; Institute of Medicine, 2002;Maris, 2002; U.S. Department of Health and Human Services, 1999); however, most of the interpersonal variability in suicide risk remains unexplained and the evidence about the populationlevel drivers of suicide rates remains underexplored. Identifying factors that influence the population suicide rate, such as climate (Adjacic-Gross et al, 2006), seasonal allergens (Postolache et al, 2005), relative income inequality (Miller et al, 2005), and urbanicity (Qin, 2005) is critical for understanding the contextual elements of suicide risk (Hawton & van Heeringen, 2009;Institute of Medicine, 2002).…”
mentioning
confidence: 99%